POLR3-related leukodystrophy caused by biallelic POLR3A and 1C pathogenic variants: a single-center experience - Liu, Jing; Niu, Yue; Qin, Jiong; Yang, Zhixian (Frontiers in Neurology, 2024)
Objectives This study aimed to investigate the clinical, radiological, and genetic features of POLR3-related leukodystrophy caused by mutations in POLR3A or POLR1C. Methods Fourteen Chinese patients with POLR3-related leukodystrophy were enrolled in this cross-sectional observational study. The clinical manifestations, brain MRI and genetic tests of the patients were evaluated. Results Thirteen patients had biallelic variants in POLR3A (92.9%), and one had biallelic variants in POLR1C (7.1%). The median age at disease onset was 9 months. A total of 85.7% of the patients presented with motor delay, abnormal gait, and intelligence disability in the first 2 years of life. Intellectual disability can be categorized based on its severity. It varied from mild (which involves difficulty concentrating) to very severe (with no smiling or laughing or never being able to speak since birth). Short stature was observed in all patients, and delayed dentition was observed in 64.3% of them. Furthermore, three out of 14 patients had myopia. Hypomyelination was invariably present in all patients, whereas myelination of the basal ganglia was preserved in only six out of 14 patients. All the mutations were compound heterozygous and included missense (n = 25), deletion (n = 1), and splice site variants (n = 2). A total of 78.6% of the patients with POLR3A were identified as carrying the c.1771-6C>G variant or the c.1771-7C>G variant. Conclusion The phenotypic diversity of POLR3-HLD associated with pathogenic variants ranges from mild to very severe for neurological and non-neurological symptoms. Most patients presented symptoms in the first 2 years of life. The c.1771-6C>G or c.1771-7C>G variant is the most frequent mutation site in POLR3A in Chinese individuals.